Glutamate Chemical Exchange Saturation Transfer (GluCEST) Magnetic Resonance Imaging of Rat Brain With Acute Carbon Monoxide Poisoning - Yuan Xu; Zerui Zhuang; Hongyi Zheng; Zhiwei Shen; Qilu Gao; Qihuan Lin; Rong Fan; Liangping Luo; Wenbin Zheng (Frontiers in Neurology, 2022)
ObjectivesTo evaluate the diagnostic and prognostic values of glutamate chemical exchange saturation transfer (GluCEST) magnetic resonance imaging as a quantitative method for pathogenetic research and clinical application of carbon monoxide (CO) poisoning-induced encephalopathy combined with the proton magnetic resonance spectroscopy (1H-MRS) and the related histopathological and behavioral changes.MethodsA total of 63 Sprague–Dawley rats were randomly divided into four groups. Group A (n = 12) was used for animal modeling verification; Group B (n = 15) was used for magnetic resonance molecular imaging, Group C (n = 15) was used for animal behavior experiments, and Group D (n = 21) was used for histopathological examination. All the above quantitative results were analyzed by statistics.ResultsThe peak value of carboxyhemoglobin saturation in the blood after modeling was 7.3-fold higher than before and lasted at least 2.5 h. The GluCEST values of the parietal lobe, hippocampus, and thalamus were significantly higher than the base values in CO poisoning rats (p < 0.05) and the 1H-MRS showed significant differences in the parietal lobe and hippocampus. In the Morris water maze tests, the average latency and distance were significantly prolonged in poisoned rats (p < 0.05), and the cumulative time was shorter and negatively correlated with GluCEST.ConclusionThe GluCEST imaging non-invasively reflects the changes of glutamate in the brain in vivo with higher sensitivity and spatial resolution than 1H-MRS. Our study implies that GluCEST imaging may be used as a new imaging method for providing a pathogenetic and prognostic assessment of CO-associated encephalopathy.